Deep Brain Stimulation in Parkinson's Disease: Still Effective After More Than 8 Years. Issue 7 (21st September 2020) - Thomsen, Birgitte L.C.; Jensen, Steen R.; Clausen, Anders; Karlsborg, Merete; Jespersen, Bo; Løkkegaard, Annemette
ABSTRACT: Background: Deep brain stimulation of the subthalamic nucleus (STN‐DBS) is well established and the most effective treatment for advanced Parkinson's disease (PD). However, little is known of the long‐term effects. Objectives: The aim of this study was to examine the long‐term effects of STN‐DBS in PD and evaluate the effect of reprogramming after more than 8 years of treatment. Methods: A total of 82 patients underwent surgery in Copenhagen between 2001 and 2008. Before surgery and at 8 to 15 years follow‐up, the patients were rated with the Unified Parkinson's Disease Rating Scale (UPDRS) with and without stimulation and medicine. Furthermore, at long‐term follow‐up, the patients were offered a systemic reprogramming of the stimulation settings. Data from patients' medical records were collected. The mean (range) age at surgery was 60 (42–78) years, and the duration of disease was 13 (5–25) years. A total of 30 patients completed the long‐term follow‐up. Results: The mean reduction of the motor UPDRS by medication before surgery was 52%. The improvement of motor UPDRS with stimulation alone compared with motor UPDRS with neither stimulation nor medication was 61% at 1 year and 39% at 8 to 15 years after surgery (before reprogramming). Compared with before surgery, medication was reduced by 55% after 1 year and 44% after 8 to 15 years. After reprogramming, most patients improved. Conclusions: STN‐DBS remains effective in the long run, with a sustained reduction of medication in the 30 of 82 patients available for long‐term follow‐up. Reprogramming is effective even in the late stages of PD and after many years of treatment. Abstract : View Supplementary Video 1